Theology as an empirical science - Macintosh, Douglas Clyde, 1877-1948 (Routledge library editions. Philosophy of religion ;, 2013)
Investigating the question 'can theology, description of the divine reality, be made truly scientific?', this book addresses logic and human knowledge alongside experimental religion. An important philosophic work by a prolific theologian also known for his later court case regarding conscientious objection, this book describes how it is possible to relate theological theory with religious experience of the divine the way that the sciences relate to human acquaintance with things and people in social experience.